2010
DOI: 10.1038/jhg.2010.100
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphisms of the endothelial nitric oxide synthase gene in breast cancer: a genetic association study and meta-analysis

Abstract: The endothelial nitric oxide synthase gene (NOS3) has been proposed as a candidate gene for breast cancer (BC), however, the specific role of variants and haplotypes has not been clarified. We examined the association of two polymorphisms (4b/a and G894T) and their haplotypes in a case-control sample of 306 patients with BC and in 131 healthy females. In addition, a meta-analysis of studies investigating association between NOS3 polymorphisms and BC was conducted. The single locus analysis for the two polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…As observed in another meta-analysis which indicates that 894G has no association with cancer susceptibility, however the 786T polymorphism were associated with breast cancer risk [229]. The same study notes that some meta-analysis studies have used duplicated data and consequently could explain the inconsistancies in the literature, for instance in a study conducted by Zintzaras et al [230]. While there was agreement between 786T, there was no such agreement for 894G.…”
Section: Oncogenes and Tumor Suppressors Regulate Ip3r But Little Datmentioning
confidence: 56%
“…As observed in another meta-analysis which indicates that 894G has no association with cancer susceptibility, however the 786T polymorphism were associated with breast cancer risk [229]. The same study notes that some meta-analysis studies have used duplicated data and consequently could explain the inconsistancies in the literature, for instance in a study conducted by Zintzaras et al [230]. While there was agreement between 786T, there was no such agreement for 894G.…”
Section: Oncogenes and Tumor Suppressors Regulate Ip3r But Little Datmentioning
confidence: 56%
“…In addition, we further excluded one study [9] which deviated from Hardy-Weinberg equilibrium in controls and included one recent study by Zintzaras et al [2], and re-assessed the association between eNOS G894T polymorphism and breast cancer under co-dominant model, dominant model and recessive model (Figs. 1, 2, 3, 4).…”
Section: To the Editormentioning
confidence: 99%
“…The results indicated that eNOS G894T polymorphism was associated with breast cancer (TT vs. GG: odds ratio (OR) = 1.22, 95% confidence interval (CI) = 1.02-1.44; recessive model: OR = 1.21, 95% CI = 1.02-1.42). However, another recent meta-analysis by Zintzaras et al [2] suggested that there was non-significant association between eNOS G894T polymorphism and breast cancer (T vs. G: OR = 1.06, 95% CI = 0.97-1.16; recessive model: OR = 1.19, 95% CI 0.99-1.43).After carefully inspecting the two studies, it was noted that in the study by Hao et al [1], there were two methodological issues which did influence the conclusion.First, they included three studies [3-5] which didn't investigate the association between eNOS G894T polymorphism and breast cancer. Actually, the two studies [3,4] examined the association between polymorphisms and breast cancer outcomes (such as recurrence and death, and so on).…”
mentioning
confidence: 95%
“…In cancers such as non -small cell lung cancer (Fujita et al 2010), acute lymphoblastic leukemia (ALL), and breast cancer there is evidence to suggest that NOS3 mutations can affect disease susceptibility (Haas et al 2009;Hao et al 2010;Zintzaras et al 2010). Such susceptibility might be a result of increased angiogenic activity and a consequently decreased threshold for the angiogenic switch.…”
Section: Nitric Oxide Synthase (Nos3/enos)mentioning
confidence: 99%